SENSLOPE v. 2 development and evaluation of alternative cost-effective instrumentation for monitoring landslides on real world slopes - Libao, Franz Joseph; Lozano, Al John Lexter; Sandoval, Andrew (2010)
This work focuses on preparing an alternative landslide monitoring system for a deployment on a real world slope. The system consists of a sensor column array, which currently has tilt and soil moisture sensor boards based on PIC microcontrollers. An accelerometer-based ground shaking node is added to the sensor array to measure ground vibrations as these can trigger landslides. Bootloading through the Controller Area Network (CAN) is featured on the sensor column arrays for field programmability. An improved CAN scheduling algorithm is implemented to accommodate more messages on the CAN bus. More characterization tests on the type of soil expected in the deployment is made on the soil moisture sensor. A polyethylene (PE) pipe is used as packaging for the array and is tested for waterproofing and strength. The sensor array has a base station which gathers, processes, displays, and interprets the data using a Python-based GUI built for improved long time operation and better usability. Two systems will be deployed on the real world slope: one at the toe and one at the berm. The base stations of the two systems will be connected to each other via wireless LAN. In coordination with NIGS, this system will be used to study the soil dynamics of a slope in Benguet, where numerous landslides have occurred recently.
Thesis (B.S. Electronics and Communications Engineering) -- University of the Philippines, Diliman.
Keywords: Landslides -- Monitoring; Controller Area Network (Computer network); Soil dynamics; SENSLOPE